Pengaruh Reward dan Punishment terhadap Kinerja Karyawan pada PT Bank Nagari Cabang Utama Sumatera Barat - Jhon Fernos; Ega Zulfa Yolanda (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The provision of rewards and punishments will affect employee performance. If the rewards and punishments given are not in accordance with the rights and obligations of employees, this can reduce their performance. The purpose of this study was to determine the effect of rewards and punishments on employee performance at Bank Nagari, Main Branch of West Sumatra. Through the sample questionnaire method using the Yamane technique, there were 163 respondents who were used as samples in this study. In the hypothesis testing that has been carried out, it can be concluded that rewards have a positive and significant effect on employee performance at Bank Nagari, Main Branch of West Sumatra and punishment has a positive and significant effect on employee performance at Bank Nagari, Main Branch of West Sumatra.